Exploring the concept of Kota Kinabalu city as an urban ecotourism destination - Nattana Simon; Fiffy Hanisdah Saikim; Awangku Hassanal Bahar Pengiran Bagul (Penerbit UMT, 2021)
The concept of ecotourism which applies to tourism activities in natural and undisturbed environments, is frequently thought to be antonymous with urban environments, however, can be proven possible. Despite Sabah being well regarded for its ecotourism sector, the concept of urban ecotourism in the city of Kota Kinabalu has yet to be explored. Existing ecotourism destinations in Sabah are facing carrying capacity problems thus there is a growing need to explore new and different destinations or attractions to meet the demand of tourists. This study examined local Kota Kinabalu residents and tourists’ perception and values pertaining to the potential of Kota Kinabalu as an urban ecotourism destination as well as how preservation of green spaces in cities encouraged sustainability using a multi-methodological approach. Based on the results of this study, both respondent groups ranked Kota Kinabalu city as having a high potential as an urban ecotourism destination. In addition, the results of this study could assist decision or policymakers in the local tourism sector with tourism development decisions.